Observando la evolución del sector informal desde el espacio: Un enfoque municipal 2013-2020 - Erick Rangel González; Irving Llamosas-Rosas (Banco de México, 2021)
– This document presents an alternative to measure informal economic activity at the municipal level for the 2013-2020 period in Mexico. Using satellite images of nightlight and microdata from the 2019 Economic Census, the formal and informal Value Added at the municipal level is estimated using a modified version of the model proposed by Tanaka and Keola (2017). Although there are some measurements in Mexico of informal economic activity, these are not available at the municipal level or on an annual basis. The results indicate that at the national level, most of the municipalities show decreases in their levels of informal activity during the 2013-2019 period, with the North and North central regions concentrating a higher proportion of these, while in the Center the majority of the municipalities remained unchanged in the percentage of informal Value Added. In contrast, an important part of the Southern municipalities registered increases in the percentage of their informal activity during the same period.
Keywords: E01; E26; C53; C55; O54; 330; Informality; Value Added; Satellite Images of Luminosity; Municipalities